Targeting Growth Factor Signaling Pathways in Pancreatic Cancer: Towards Inhibiting Chemoresistance - Xelwa, Ntombikayise; Candy, Geoffrey Patrick; Devar, John; Omoshoro-Jones, Jones; Smith, Martin; Nweke, Ekene Emmanuel (Frontiers in Oncology, 2021)
Pancreatic cancer is one most deadly cancers, ranking amongst the top leading cause of cancer related deaths in developed countries. Features such as dense stroma microenvironment, abnormal signaling pathways and genetic heterogeneity of the tumors contributes to its chemoresistant characteristics. Amongst these features, growth factors have been observed to play crucial roles in cancer cell survival, progression, and chemoresistance. Here we review the role of the individual growth factors in pancreatic cancer chemoresistance. Importantly, the interplay between the tumor microenvironment and chemoresistance is explored in the context of pivotal role played by growth factors. We further describe current and future potential therapeutic targeting of these factors.